Pembelajaran Multiliterasi Pada Mahasiwa Pendidikan Guru Sekolah Dasar - Delora Jantung Amelia; Bahrul Ulum; Ima Wahyu Putri Utami (Journal on Education, 2024)
Paradigm changes in the 21st century require students to change their approach which focuses on developing skills ranging from critical thinking, creativity, communication and collaboration. The type of research used in this research is qualitative research. The research model used in this research is a descriptive model that describes the implementation of multiliteracy learning for elementary school teacher education students in preparing themselves for the independent curriculum. Based on the objectives of this research, the research design is to use a qualitative approach. With the main aim of analyzing phenomena or events that appear in reality without any data manipulation. The research results show that PGSD students can implement a multiliteracy learning model that can integrate critical thinking in producing works of art. The pre-phase involves preparation for the introduction of multiliteracy concepts, the activity phase involves student interaction in applying critical thinking skills, and the post-activity phase involves reflection and consolidation of learning.